Dampak Kabut Asap terhadap Kinerja Usaha Pedagang Pasar di Kota Rengat Kabupaten Indragiri Hulu Provinsi Riau - Ivalaina Astarina; Syahmardi Yacob; Febblina Daryanes; Khusnul Fikri; Ahmad Ramadhan (J-MAS (Jurnal Manajemen dan Sains), 2020)
The purpose of the research in IIS to know and analyze the impact of the haze on the performance of business traders market. This research belongs to the type of descriptive research. Descriptive research that aims to describe, describe and analyse existing events and aims to obtain information about the impact of haze in accordance with existing theories. Data collection method through dissemination of questionnaires and questions answered. The population in this study is the market merchant of Rengat City. Determination of sample count of 100 respondents/market trader. The data analysis technique used to analyze this research data is to be descriptively used statistical analysis in the form of a percentage formula because its purpose is to see the trend of the indicators of each variable and the research is only aimed to describe the reality in the field is not to be seen relations or comparisons. In this study, researchers used Likert measurement scales. The Likert scale relates to a statement about a person's attitude toward something.  The results of this study can be concluded that: (1) The health of the market traders of the city of Rengat is interrupted because of the thick haze that affects the trading activity itself. (2) The income of market traders in the city of Rengat is decreasing due to declining people's desire to shop in the market due to the worry of being exposed to haze which can cause ISPA disease and other health disorders. (3) The market environment of the Rengat is affected by the smoke of the daily Trader's life. Usually traders have already held their trades starting from the beginning of the morning, because the haze of most traders often come late to the market (overdo). (3) The education of students from the family of market traders in the city of Rengat is also affected by the haze so that it must be dissolved until normal weather conditions are back. Because of this, students have a lot of missed material and have to force themselves to pursue the lag by adding hours and learning tasks that are much beyond the student's thinking capacity.